Redefining biological sex : a place for the intersex - Tan, Penny Pin (Nanyang Technological University, 2020)
Biological sex is commonly understood and accepted as a strict dichotomy with clear categorical boundaries. However, the nature of biological sex is far more complicated than what culture has presented it to be. In this paper I seek to understand the social construction of biological sex under a dominant gender dimorphic framework through exploring the gap between science and ideology. I refer to Judith Butler’s notion of sex as gendered to navigate through the various ways in which society has attempted to fix inconsistencies with the binary view of sex, which has both theoretical and practical implications pointing towards the incompleteness of the current definition. I argue that the traditional notion of biological sex should be redefined in light of sex variations that render the commonsense view theoretically flawed, which has further led to a series of unethical social consequences bearing on those who possess such anatomical differences.